2021
DOI: 10.3390/jpm11050391
|View full text |Cite
|
Sign up to set email alerts
|

Differences among COVID-19, Bronchopneumonia and Atypical Pneumonia in Chest High Resolution Computed Tomography Assessed by Artificial Intelligence Technology

Abstract: The aim of this study was to compare the results of automatic assessment of high resolution computed tomography (HRCT) by artificial intelligence (AI) in 150 patients from three subgroups: pneumonia in the course of COVID-19, bronchopneumonia and atypical pneumonia. The volume percentage of inflammation and the volume percentage of “ground glass” were significantly higher in the atypical (respectively, 11.04%, 8.61%) and the COVID-19 (12.41%, 10.41%) subgroups compared to the bronchopneumonia (5.12%, 3.42%) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…However, doubts soon arose about the specificity of the identification of COVID-19 pneumonia and the need to differentiate it from other causes of pneumonia [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, doubts soon arose about the specificity of the identification of COVID-19 pneumonia and the need to differentiate it from other causes of pneumonia [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for the high false-positive rate of chest CT in asymptomatic patients is that many diseases can radiologically mimic COVID-19 pneumonia, including other forms of viral pneumonia [ 22 , 23 ], atypical pneumonia [ 24 ], interstitial pneumonia [ 3 , 8 , 12 , 21 , 22 ], drug-induced pneumonia [ 21 , 25 , 26 ], and traumatic changes such as rib fractures [ 27 ]. Our results suggested that unknown early or mild interstitial pneumonia and bilateral lower lobe dorsal lung collapse due to poor inspiration were difficult to differentiate from mild COVID-19 pneumonia, which supports the findings of previous reports [ 3 , 8 , 12 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with COVID-19, we also noted the clinical and radiological symptoms of lung involvement. HRCT (high resolution computed tomography) images were analysed by the artificial intelligence technology software YITU Healthcare to automatically measure the relative (%) volume of inflammation in both lungs (the methodology was as described in a previous work from our centre) [13]. The chest X-ray images were assessed by a radiologist using a semiquantitative chest X-ray severity score [14].…”
Section: Methodsmentioning
confidence: 99%